Evaluation of postoperative feeding strategies in children with intestinal atresia: A single-center retrospective study - Wang, Jiepin; Xu, Haozhong; Wang, Junxiang; Xiao, Dong (Frontiers in Pediatrics, 2022)
Objectives: Postoperative enteral nutrition has a significant influence on the prognosis of patients with congenital intestinal atresia. Currently, there is no precise guidance on enteral nutrition management. This study aimed to compare the outcomes of different feeding strategies based on the initial volume and daily advancement in postoperative patients with congenital intestinal atresia.  Methods: This study was a retrospective study collected from October 2019 to July 2021 in Shenzhen Children’s Hospital. According to the initial volume and daily advancement, the patients were divided into high-dose group and low-dose group. General basic information such as age, sex, and lesion type was gathered. The postoperative outcome included the levels of hemoglobin (HGB), albumin (ALB), alanine aminotransferase (ALT), aspartate aminotransferase (AST), direct bilirubin (DB), length of stay, length of total PN, time to reach 100% enteral nutrition (EN) (120 kcal·kg-1·d-1), infection incidence and intestinal failure associated liver disease (IFALD) incidence(DB>2mg·dL-1). Results: In total, 32 patients with congenital intestinal atresia were identified. There was no significant difference between the high-dose group and the low-dose group in the baseline characteristic. The length of time to reach 100% (p=0.001) enteral nutrition and postoperative hospital stay (p=0.092) were shorter in the high-dose group. In the high-dose group, patients at discharge were with not only lower levels of DB (p=0.009), AST(p=0.109) and ALT(p=0.045) but also higher level of ALB (p=0.459) and hemoglobin (p=0.354). The incidence of IFALD was significantly lower in the high-dose group(p=0.032). There was no significant difference in the overall incidence of postoperative complications.  Conclusions: Within the limitations, the findings of this study suggest that High-dose feeding (initial volume>15ml·kg-1·d-1, daily advancement>10ml·kg-1·d-1) is beneficial for the prognosis of patients diagnosed with congenital intestinal atresia treated by intestinal